1988
DOI: 10.1042/bj2551045
|View full text |Cite
|
Sign up to set email alerts
|

Guanine for DNA synthesis. A compulsory route through ribonucleotide reductase

Abstract: Two alternative pathways for the synthesis of dGTP and its incorporation into DNA were studied: guanine (Gua)----GMP----GDP----dGDP----dGTP----DNA and dG----dGMP----dGDP----dGTP----DNA. To determine the contribution of each pathway to DNA synthesis independently of each other, [14C]Gua and [3H]dG tracer experiments were performed in a double-mutant S-49 mouse T-lymphoma cell line, dGuo-L, with purine nucleoside phosphorylase (EC 2.4.2.1)-deficiency and dGTP-feedback-resistant ribonucleotide reductase (RR, EC 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1990
1990
2008
2008

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…However, these signaling pathways are only the potential downstream targets; the upstream mechanisms that sense the depletion of guanine nucleotide and trigger the cell cycle arrest or apoptosis are still not very clear. Interestingly, it has been shown that certain specific inhibitors of ribonucleotide biosynthesis, including MPA, cause a reversible p53-dependent G 1 arrest, and p53 has been proposed to serve as a sensor of ribonucleotide pool perturbation (20), although MPA has been shown to inhibit DNA synthesis (21,22). p53 has also been shown to mediate the cell cycle arrest and apoptosis in response to guanine nucleotide depletion in human neuroblastoma cell lines (17, 23).…”
Section: Inosine Monophosphate Dehydrogenase (Impdh)mentioning
confidence: 99%
“…However, these signaling pathways are only the potential downstream targets; the upstream mechanisms that sense the depletion of guanine nucleotide and trigger the cell cycle arrest or apoptosis are still not very clear. Interestingly, it has been shown that certain specific inhibitors of ribonucleotide biosynthesis, including MPA, cause a reversible p53-dependent G 1 arrest, and p53 has been proposed to serve as a sensor of ribonucleotide pool perturbation (20), although MPA has been shown to inhibit DNA synthesis (21,22). p53 has also been shown to mediate the cell cycle arrest and apoptosis in response to guanine nucleotide depletion in human neuroblastoma cell lines (17, 23).…”
Section: Inosine Monophosphate Dehydrogenase (Impdh)mentioning
confidence: 99%
“…The dramatic differences in dGTP accumulation in G1-and S-phase cells can resolve this paradox. G.-phase NSU-1 and dGuo-L cells slowly and extensively accumulate dGTP (for kinetics see [25]), whereas S-phase cells show a much faster turnover rate because of ongoing DNA synthesis, and hence accumulate much less dGTP from dG. Further, we have previously shown that the direct synthesis of dGTP from dG has limited capacity relative to dGTP utilization for DNA synthesis [25].…”
Section: Discussionmentioning
confidence: 99%
“…G.-phase NSU-1 and dGuo-L cells slowly and extensively accumulate dGTP (for kinetics see [25]), whereas S-phase cells show a much faster turnover rate because of ongoing DNA synthesis, and hence accumulate much less dGTP from dG. Further, we have previously shown that the direct synthesis of dGTP from dG has limited capacity relative to dGTP utilization for DNA synthesis [25]. The drastically lower dGTP accumulation in S-phase compared with G,-phase cells is expected to mitigate dG effects specifically in S-phase cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation